A retrospective cohort study on the impact of finerenone on the hepatic fibrosis indicator FIB-4 - An, Bo; Chen, Fang; An, Wencheng; Cui, Zhijun; Jiang, Lin; Zhou, Shujing; Song, Mingda; Huang, Wei; Yan, Huixian (Frontiers in Endocrinology, 2026)
ObjectiveThis study aimed to evaluate the influence of finerenone, a novel nonsteroidal selective mineralocorticoid receptor antagonist (nsMRA), on the hepatic fibrosis indicator FIB-4, as well as its safety profile in hospitalized patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) managed in the endocrinology department.Methods:A single-center, retrospective cohort design was employed, enrolling 138 consecutive hospitalized patients who initiated finerenone therapy for the first time in our endocrinology department between June 2023 and December 2024. Baseline data and subsequent outpatient follow-up records were extracted to calculate the FIB-4 and assess changes in hepatic and renal function, serum potassium levels, and adverse events during treatment.ResultsOf the enrolled cohort, 119 patients (85.6%) had complete baseline laboratory profiles, with a mean age of 63.1 years and 58% male. Baseline FIB-4 median 1.15. Among 52 patients (43%) who completed follow-up, the median follow-up duration was 6 months (range 1–16 months). The median follow-up FIB-4 declined to 1.10, representing an absolute reduction of 0.05. Patients with follow-up exceeding 12 months follow-up showed a further reduction to 0.96. Importantly, no cases of treatment discontinuation due to hyperkalemia were documented during follow-up.ConclusionIn real-world clinical practice, finerenone in T2DM patients with CKD trended to lower FIB-4 values, especially with longer use. However, no statistical significance and study limitations preclude definitive conclusions on its antifibrotic activity. These findings are hypothesis-generating and need confirmation in large, prospective, long-term studies with robust endpoints and proper controls.